Describing Adolescent Breastfeeding Environments Through Focus Groups in an Urban Community - Nikki Keene Woods; Amy K. Chesser; Jennifer Wipperman (SAGE Publishing, 2013)
Purpose: Breastfeeding is a potential solution to improve health outcomes for adolescent mothers and infants. Adolescence is a risk factor for low breastfeeding rates and is associated with a higher risk for perinatal complication. This study investigated facilitators and barriers to adolescent breastfeeding initiation and duration in an urban setting. Methods: Four, 1-hour focus groups were conducted. Twenty-nine (N = 29) adolescent mothers and pregnant adolescents participated and described attitudes toward breastfeeding, attitudes among family and friends, current knowledge, and barriers and facilitators for breastfeeding. Results: Four themes emerged, including the following: behavioral histories of breastfeeding, community assets, social support, and barriers. Participants identified positive histories and community resources such as local hospitals and social services as facilitators. Lifestyle, independence, lack of support from family and primary care providers, social stigma/embarrassment, and difficulty with breastfeeding techniques were described as barriers. Conclusion: A comprehensive and integrated primary care and public health community effort is needed to support and improve adolescent breastfeeding. Further examination of integrated interventions focused on adolescent breastfeeding behaviors through an environmental approach is needed.